Organizational behaviour and work : a critical introduction - Wilson, Fiona M. (2018)
A critical yet accessible introduction to organisational behaviour and work, this book will help you understand the complexities of organisational life and evaluate modern business practices. Classic organisational behaviour topics such as team-working, motivation, and change are complemented by core critical approaches such as power and control, organisational misbehaviour, and health and well-being through a clear three-part structure. Students are encouraged to look beyond a descriptive approach and truly engage with the content. Examples and 'Stop and Think' boxes placed throughout chapters, as well as end-of-chapter case studies with accompanying questions, provide the opportunity for this engagement and show how each chapter's theoretical coverage applies in real-life business situations.
Keywords: Organizational behavior -- Textbooks; Organizational behavior